2000
DOI: 10.1159/000007801
|View full text |Cite
|
Sign up to set email alerts
|

Colonization with <i>cag</i>A-Positive <i>Helicobacter pylori</i> Strains Inversely Associated with Reflux Esophagitis and Barrett’s Esophagus

Abstract: Aim: The hypothesis that colonization with cagA+ Helicobacter pylori strains protects against the development of gastroesophageal reflux disease (GERD) and its complications is tested. Methods: Patients with reflux esophagitis and Barrett’s esophagus were studied. Antral biopsy specimens were obtained for detection of H. pylori. A serum sample was obtained for determination of IgG antibodies to H. pylori and to the CagA protein. Results: 736 patients were studied. 118 patients had reflux esophagitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
65
1
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 18 publications
5
65
1
4
Order By: Relevance
“…Acid reflux depends more on the integrity of the lower oesophageal sphincter, hence the insignificant effect of H pylori infection on reflux. Patients with severe reflux oesophagitis are less likely to have H pylori infection, [17][18][19][20][21][22][23][24][25][26] possibly because corpus gastritis caused by helicobacter infection limits maximum acid output in these patients, [27][28][29][30][31][32] thus protecting them against the more severe forms of reflux oesophagitis. Such people might theoretically be at risk of increased exposure of the lower oesophagus to acid after eradication of H pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…Acid reflux depends more on the integrity of the lower oesophageal sphincter, hence the insignificant effect of H pylori infection on reflux. Patients with severe reflux oesophagitis are less likely to have H pylori infection, [17][18][19][20][21][22][23][24][25][26] possibly because corpus gastritis caused by helicobacter infection limits maximum acid output in these patients, [27][28][29][30][31][32] thus protecting them against the more severe forms of reflux oesophagitis. Such people might theoretically be at risk of increased exposure of the lower oesophagus to acid after eradication of H pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…11 Most studies find no relation between H pylori infection and etiology of GERD. 12 While other studies have found a lower prevalence of H pylori infection in patients with reflux symptoms, suggesting a possible protective effect of this bacterial infection. 13 The relation between H pylori infection and GERD needs more study in order to find the effect of H pylori on GERD patients.…”
Section: Discussionmentioning
confidence: 91%
“…Recentemente, alguns trabalhos mostram que a infecção pelo H. pylori poderia ter um efeito protetor contra a doença (17,18,33,45,57) . De modo complementar, mostrou-se que pacientes infectados por linhagens mais virulentas (cagA+, vacAs1) estariam inversamente associados com o desenvolvimento da doença.…”
Section: Resultsunclassified
“…De modo complementar, mostrou-se que pacientes infectados por linhagens mais virulentas (cagA+, vacAs1) estariam inversamente associados com o desenvolvimento da doença. Deste modo, pacientes infectado por tais linhagens seriam protegidos contra complicações decorrentes do refluxo ácido (17,33,45,57) . Algumas hipóteses têm sido propostas para explicar tal fenômeno.…”
Section: Resultsunclassified